Correlation of sociodemographic profiles with psychological problems among hospitalized patients receiving unplanned hemodialysis. Issue 1 (1st January 2020) - Kao, Yu-Yin; Lee, Wen-Chin; Wang, Ruey-Hsia; Chen, Jin-Bor
Abstract: Purpose: In this prospective study, we aimed to examine the sociodemographic factors and clinical factors associated with psychological disorders in chronic kidney disease (CKD) patients receiving unplanned hemodialysis (HD). Methods: We prospectively enrolled 187 CKD stage 5 patients receiving unplanned HD at a tertiary hospital from January 2015 to December 2016. We used structured questionnaires to gather data about participants' anxiety, depression, and sleep disturbance. Generalized linear regression analysis was used to examine the relationships between sociodemographic and laboratory parameters, and severity of psychological distress. Results: The mean age of the participants was 60 years, and the number of men and women was 97 and 90, respectively. We did not find a significant association between anxiety, depression, and sleep disturbance scores and gender, age, marital status, religion status, education levels, and employment status and number of comorbidities. Generalized linear regression analysis showed that a multidisciplinary CKD care program in outpatient clinic disclosed a significant negative association with psychological disorders in participants. Conclusions: CKD patients exhibited psychological distress when receiving unplanned HD, not closely associated with sociodemographic profiles.